2024
DOI: 10.1021/acsbiomaterials.3c01786
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and Antimicrobial Properties of Boron Nitride/Methacrylic Acid Quaternary Ammonium Composites Reinforced Dental Flowable Resins

Yuting Wang,
Shengjie Xiao,
Siyi Lv
et al.

Abstract: Dental resin composites (DRCs) are commonly used to restore teeth affected by dental caries or defects. These materials must possess excellent properties to withstand the complex oral environment. The objective of this study was to prepare and characterize Boron nitride nanosheets (BNN)/ dimethyl amino hexadecyl methacrylate (DMAHDM) composites (BNN/DMA), and to evaluate them as functional fillers to enhance the mechanical and antimicrobial properties of dental resins. The BNN/DMA composites were successfully … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 56 publications
0
0
0
Order By: Relevance
“…Several studies have demonstrated the potent antibacterial properties of DMAHDM monomers when incorporated into composite resins [22,25,42], cement [16], and root canal sealers [43]. Xiao et al (2019) developed a novel multifunctional nanocomposite for root caries restorations to inhibit periodontitis-related pathogens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have demonstrated the potent antibacterial properties of DMAHDM monomers when incorporated into composite resins [22,25,42], cement [16], and root canal sealers [43]. Xiao et al (2019) developed a novel multifunctional nanocomposite for root caries restorations to inhibit periodontitis-related pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…The degree of conversion (DC) was evaluated using an FT-IR spectrometer (Nicolet 6700, Thermo Fisher Scientific, Waltham, MA, USA) (400−4000 cm −1 wavelength and 32 scans at 4 cm −1 resolution) using the relative band ratio method. The technique estimates the amount of methacrylate groups remaining after exposure to light by measuring the change in intensity of the peak of the C=C vibration at 1637 cm −1 , with the absorbance peak of the aromatic group at 1583 cm −1 as an internal reference [ 21 , 22 ]. A drop of the resin material (mean sd; n = 3) was placed on the attenuated total reflectance (ATR) crystal, covered with a mylar strip, and was then measured before and after light curing for 40 s (1200 mW/cm 2 , Labolight, DUO, GC, Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…Researchers have attempted to enhance dental resins by adding various materials, including nano- and micro-sized fillers, whiskers, and fibers. Incorporating silane-treated nanohydroxyapatite-filled zinc oxide could significantly improve the physical, mechanical, and thermal properties of dental composite materials [ 64 ]. It was pointed out that addition of an appropriate amount of silica filler in composites can enhance mechanical properties [ 65 , 66 ].…”
Section: Applications Of Self-healing Microcapsules In Dental Compositesmentioning
confidence: 99%
“…In addition, there was a study on the addition of DMAHDM, NACP and microcapsules to dental adhesive resins [ 86 ]. Via experimental confirmation, a new antimicrobial resin adhesive with self-healing functions that could be used for clinical applications was developed [ 64 , 87 , 88 , 89 ].…”
Section: Applications Of Self-healing Microcapsules In Dental Compositesmentioning
confidence: 99%